Antihyperglycemic, Antihyperlipidemic, and Antioxidant Effects of Morin on Streptozotocin-Induced Diabetic Rats - A. Beyatli; N. Gül; Ş. Coşkun Cevher; N. Arı (Eurasian Chemico-Technological Journal, 2024)
Recently, natural remedies for the management of diabetes observed a rise in interest as a result of the negative impacts of conventional treatment. The present work studies the beneficial effects of morin in normal and streptozotocin-induced diabetic rats on glucose levels, tissue antioxidant state, and lipid peroxidation. Oral delivery of morin (25 and 50 mg/kg body weight/day) for 21 days to normal and diabetic rats could not prevent weight loss, but consumption of food and water (25 mg/kg) was considerably reduced. Morin substantially decreased glucose, total cholesterol, triglycerides, LDL cholesterol, and VLDL cholesterol in the blood of diabetic rats. Additionally, it greatly halted the rise in aspartate aminotransferase and alanine aminotransferase levels as well as the decline in HDL cholesterol levels in diabetic rats. In comparison to normal rats, diabetic rats had higher levels of malondialdehyde, lower levels of nitric oxide, decreased glutathione, and lower levels of superoxide dismutase in their hepatic, renal, and pancreatic tissues. The morin treatments substantially reduced the levels of hepatic and pancreatic reduced glutathione, hepatic and pancreatic reduced nitric oxide, and hepatic, renal, and pancreatic superoxide dismutase. They also prevented the increase of hepatic, renal, and pancreatic malondialdehyde. Histopathological findings revealed a reduction in pancreatic damage in morin-treated rats. Morin exerts antihyperglycemic, antihyperlipidemic, and antioxidant activities in diabetic rats.